Celebrating Diversity in Every Classroom: Culturally Responsive Perspectives on Video Analysis for Teacher Development - Henrikson, Robin; Lau, Wing Shuen (International Dialogues on Education Journal, 2022)
Teacher education programs and professional learning programs have increasingly offered opportunities for in-service teachers to engage in video analysis using pre-recorded video clips of teachers using instructional strategies. During the COVID-19 lockdown, teachers were only able to access online learning and teaching due to the inability to watch live classrooms in real time. In this thought piece, the authors advocate for the continued and intentional use of video observations of expert or master teachers that promote culturally responsive teaching (CRT). Integration of video observation and debriefs into teacher education programs for both preservice and in-service educators ought to not only demonstrate the application of instructional strategies being taught but would also deliberately showcase diverse master teachers and content areas in an effort to dismantle existing barriers to equitable education. While there is a persistent call for diversifying the teaching workforce, this can only be sustained with authentic and intentional efforts that ensure underrepresented pre-service and in-service teachers are reflected authentically and consistently throughout teacher preparation programs and curriculum.